Navigating through time and space: deixis in Atwood’s “This is a photograph of me” - Velasco, Yvonne Pedria (Penerbit Universiti Kebangsaan Malaysia, 2016)
This stylistics analysis of Margaret Atwood’s poem examines the persona as a paradoxical element whose interpretation was derived by applying the deictic shift theory. The use of the theory demonstrates how meaning was derived from the literary work that allows anchorpoints in time and space to position the reader. While Atwood’s poem has always been interpreted along the sphere of feminism whereby women are perceived as being marginalized and relegated to the domestic fold and are unworthy to express their identity and rise above the surface of a sea of domestic responsibilities, by using a more formalist approach, the process enabled an analysis of the theme, effects and meaning based on the language of the poem as evidentiary support. Deixis, as a linguistic feature, was employed as a tool of analysis, deriving meaning from verb tense and aspect, personal pronouns, and adverbs of time and place. These linguistic features were viewed and interpreted on the context of their utterance. Additionally, the concurrent use of the text-world theory facilitates the reader’s capacity to build the world of the text. Hence, the formalist approach employed in the analysis enabled recourse to the language of the poem that allowed the persona to be revealed.